IMPLEMENTASI CONTENT-BASED FILTERING PADA APLIKASI RADAR ZAKAT DALAM MEREKOMENDASIKAN PREFERENSI MUSTAHIK - Husni Teja Sukmana; Siti Atinah; Luh Kesuma Wardhani (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2019)
Zakat is one of the pillars of Islam which is always mentioned parallel to prayer. The problems that exist in zakat institutions in Indonesia are low level of trust in muzaki in zakat payments through official institutions and tend to distribute zakat directly to mustahik. Zakat can attract sufficient attention from Muslim intellectuals, especially in the fields of research related to the development of zakat management. However, the growing zakat information system does not make it easier for muzaki to choose mustahik preferences, even though choice recommendations of mustahik is needed to make it easier for muzaki to choose mustahik preferences. The researcher was interested in applying the concept of recommendation in the Zakat Radar application by using the content based filtering method to produce a mustahik recommendation system with the term frequency inverse document frquency (tf-idf) technique.. This system is built using the Java programming language and MySQL as a database. The mustahik recommendation system has been successfully implemented in the Radar Zakat application, which produces 5 mustahik recommendations based on the highest weighting of the similarity of mustahik criteria chosen by the user. Similarity of mustahik criteria is based on the query of mustahik criteria chosen by the user, 5 queries of mustahik criteria are mustahik income, residence, facilities, number of dependents, and mustahik employment status.